Development and promotion strategy for Kampung Seni as sustainable tourism attractions in Batam - Octavia, Kanzila Eka; I Wayan Thariqiy Kawakibi Pristiwasa (Jurnal Pariwisata Pesona, 2025)
Kampung Seni Batam is a community-driven initiative that emerged as a response to the limited cultural expression space within the industrial-dominated landscape of Batam City. This study aims to formulate relevant development and promotion strategies to position Kampung Seni as a sustainable creative tourism destination based on community participation. A descriptive qualitative approach with a case study method was employed, with data collected through field observations, in-depth interviews, and digital documentation. The findings reveal that Kampung Seni possesses strong potential supported by organic community involvement, local cultural identity, and creative activities that encourage direct interaction between artists and visitors. However, limited structured digital promotion, the absence of formal institutional support, and the lack of educational tourism packages remain key challenges in destination development. The integration of the Triple Bottom Line framework (People, Planet, Profit) and the STP approach (Segmenting, Targeting, Positioning) produces a community-based promotion strategy that emphasizes authentic experience and narrative through the tagline “Experience Local Art, Meet the Community.” This research contributes to the development of a replicable model for community-based creative destinations as an alternative form of urban tourism development.